C-C bond formation and related reactions at the CNC backbone in (smif)FeX (smif = 1,3-di-(2-pyridyl)-2-azaallyl): Dimerizations, 3 + 2 cyclization, and nucleophilic attack; Transfer hydrogenations and alkyne trimerization (X = N(TMS)2, dpma = (Di-(2-pyridyl-methyl)-amide)) - Frazier, Brenda A.; Williams, Valerie A.; Wolczanski, Peter T.; Bart, Suzanne C.; Meyer, Karsten; Cundari, Thomas R.; Lobkovsky, Emil B. (Inorganic Chemistry, 2013)
Molecular orbital analysis depicts the CNC backbone of the smif (1,3-di-(2-pyridyl)-2-azaallyl) ligand as having singlet diradical and/or ionic character where electrophilic or nucleophilic attack is plausible. Reversible dimerization of (smif)FeN(SiMe) (1) to [(MeSi)NFe](μ-κ, κ-N,py-smif,smif) (2) may be construed as diradical coupling. A proton transfer within the backbone-methylated, and o-pyridine-methylated smif of putative (MeMesmif)FeN(SiMe) (8) provides a route to [(MeSi)NFe](μ- κ,κ-N,py,C-(Me, CH,Me(smif)H)) (9). A 3 + 2 cyclization of ditolyl-acetylene occurs with 1, leading to the dimer [2,5-di(pyridin-2-yl)-3,4-di-(p-tolyl-2,5-dihydropyrrol-1-ide)FeN(SiMe )] (11), and the collateral discovery of alkyne cyclotrimerization led to a brief study that identified Fe(N(SiMe )(THF) as an effective catalyst. Nucleophilic attack by (smif)Fe (13) on BuNCO and (2,6-Pr CH)NCO afforded (RNHCO-smif)Fe (14a, R = Bu; 14b, 2,6-PrCH). Calculations suggested that (dpma)Fe (15) would favorably lose dihydrogen to afford (smif)Fe (13). H-transfer to alkynes, olefins, imines, PhNNPh, and ketones was explored, but only stoichiometric reactions were affected. Some physical properties of the compounds were examined, and X-ray structural studies on several dinuclear species were conducted. © 2013 American Chemical Society.